JNK signaling prevents biliary cyst formation through a CASPASE-8-dependent function of RIPK1 during aging - Müller, Katrin; Honcharova-Biletska, Hanna; Koppe, Christiane; Egger, Michèle; Chan, Lap Kwan; Schneider, Anne T.; Küsgens, Lena; Böhm, Friederike; Boege, Yannick; Healy, Marc E.; Schmitt, Johannes; Comtesse, Sarah; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
The c-Jun N-terminal kinase (JNK) signaling pathway mediates adaptation to stress signals and has been associated with cell death, cell proliferation, and malignant transformation in the liver. However, up to now, its function was experimentally studied mainly in young mice. By generating mice with combined conditional ablation of Jnk1 and Jnk2 in liver parenchymal cells (LPCs) (JNK1/2LPC-KO mice; KO, knockout), we unraveled a function of the JNK pathway in the regulation of liver homeostasis during aging. Aging JNK1/2LPC-KO mice spontaneously developed large biliary cysts that originated from the biliary cell compartment. Mechanistically, we could show that cyst formation in livers of JNK1/2LPC-KO mice was dependent on receptor-interacting protein kinase 1 (RIPK1), a known regulator of cell survival, apoptosis, and necroptosis. In line with this, we showed that RIPK1 was overexpressed in the human cyst epithelium of a subset of patients with polycystic liver disease. Collectively, these data reveal a functional interaction between JNK signaling and RIPK1 in age-related progressive cyst development. Thus, they provide a functional linkage between stress adaptation and programmed cell death (PCD) in the maintenance of liver homeostasis during aging.